1993
DOI: 10.1902/jop.1993.64.11s.1129
|View full text |Cite
|
Sign up to set email alerts
|

1982‐1992: A Decade of Technology Development for Guided Tissue Regeneration

Abstract: In the last decade guided tissue regeneration (GTR) therapy has evolved in both surgical technique and membrane technology. Given new applications and membrane materials, not only must new surgical techniques be critiqued, but membrane designs must be critically examined as well. A review of historical membrane development suggests that 5 design criteria are essential: 1) tissue integration; 2) cell-occlusivity; 3) clinical manageability; 4) spacemaking; and 5) biocompatibility. These criteria may be applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
127
0
10

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(138 citation statements)
references
References 2 publications
1
127
0
10
Order By: Relevance
“…Therefore, no additional bending or cutting was required during surgery, and it satisfied the space-making and clinical manageability requirements of membrane design criteria [38].…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, no additional bending or cutting was required during surgery, and it satisfied the space-making and clinical manageability requirements of membrane design criteria [38].…”
Section: Discussionmentioning
confidence: 91%
“…[31][32][33] It has been claimed by Scantlebury that tissue integration is one of the criteria for the biomaterials to be used in the GTR technique. 34 In an another study of collagen membranes interposed between periodontal flaps and denuded root surfaces in a mongrel dog model, tissue integration was evident 10 days after implantation, and collagen membranes prevented apical migration of the epithelium during initial stages of healing. 35 A study of the biocompatibility of resorbable and nonresorbable GTR membranes in cultures of human periodontal ligament fibroblasts (HPLFs) and human osteoblast-like cells (HOLCs) also indicated that collagen membranes are very cytocompatible and may integrate into adjacent connective tissue.…”
Section: Discussionmentioning
confidence: 98%
“…1 Accordingly, GTR devices that act as passive barriers have been developed, manufactured, and marketed to support proliferation and migration of periodontal ligament cells onto the periodontally compromised tooth surface and to prevent influx from the gingival connective tissue and epithelium. 2,3 Studies have also shown that alveolar bone and cementum regeneration is critically dependent on space provision by the GTR device. [4][5][6][7][8][9] With limited space provision by the barrier membrane, alveolar bone will fill the space provided by the device.…”
Section: G Uided Tissue Regeneration (Gtr) Ismentioning
confidence: 99%